2019
DOI: 10.3390/geosciences9080331
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services Assessment and Valuation of Atmospheric Magnesium Deposition

Abstract: Ecosystem services (ES) often rely on biogeochemical cycles, but values associated with abiotic services are often ignored or underestimated. Ecosystem services from atmospheric magnesium (Mg2+) deposition are abiotic flows (wet, dry, and total), which can be considered a source of naturally-occurring fertilizer and liming material, have not been included in economic valuations of ecosystem services. Market-based valuation of these atmospheric ecosystem service flows can partially address this negative externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has a higher level of toxic effect, especially in soils with high acidity but insufficient drainage (Peres et al 2016). Especially Mg +2 has an important mission for climate regulation and carbon sequestration (Goddard et al 2007;Groshans et al 2019). Although the presence of the elements that are the subject of the study in the soil is low, their level is increasing thanks to atmospheric transports (from ocean, sea, desert dust, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It has a higher level of toxic effect, especially in soils with high acidity but insufficient drainage (Peres et al 2016). Especially Mg +2 has an important mission for climate regulation and carbon sequestration (Goddard et al 2007;Groshans et al 2019). Although the presence of the elements that are the subject of the study in the soil is low, their level is increasing thanks to atmospheric transports (from ocean, sea, desert dust, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Application of the monetary valuation of social costs and avoided social costs also depends on the user, goal, scale of the assessment, and the available data (e.g., soil survey databases, intensive field soil sampling data, etc.). For example, Mikhailova et al (2019aMikhailova et al ( , 2019b and Groshans et al (2019), reported monetary values of the avoided social cost of CO 2 emissions from SOC, SIC, and TSC stocks in the contiguous United States by soil order, soil depth, land resource region, state, and region based on data from Guo et al (2006). This type of assessment, using information from the State Soil Geographic (STATSGO) database, has a great degree of generalization which is suitable for country-level valuation but it is of limited application at the field or farm scales.…”
Section: Introductionmentioning
confidence: 99%